Histochemical Localization of Mercury in Cerebral and Cerebellar Cortices of Rats Exposed to Methyl Mercury - M., Nagendra Reddy (Indian Journal of Veterinary Anatomy, 2018)
The present study was conducted on 36 adult male Sprague Dawley rats (aged 6 weeks) to identify the localization of mercury in cerebral and cerebellar cortices of brain, which were randomly assigned into three equal groups viz. control group (group I), low methyl mercury (MeHg) exposure group (group II) and high MeHg exposure group (group III). The groups II and III were exposed to 2.5ppm and 5ppm of MeHg in the form of Methyl Mercuric Chloride (Sigma Aldrich 33368) in drinking water ad-libitum daily for 14 and 35 days of treatment periods. Autometallography technique revealed the localization of mercury particles in the motor area of cerebrum was more appreciated in 5ppm group than in 2.5ppm group at 14 days post exposure. The mercury particles were more accumulated near astrocytes, within the capillaries, neurons and neuropil of visual cortex at 14 days and 35 days post exposures. In the cerebellum, near the dendrites of neurons and the neuropil in molecular layer and also Purkinje cells showed more mercury particles in 5 ppm group and meager in 2.5ppm group at 14 and 35 days post exposure. However, granular cell layer and sub cortical white matter of cerebellum showed the presence of mercury particles in both the experimental groups at 14 days of exposure, greater in 2.5ppm than in 5ppm group at 35 days post exposure.